Escrits per obediència com a testimoni d'autories: les vides de Teresa de San Bruno (1655-1722) i Gertrudis María de la Santísima Trinidad (1660-1736). - Herrero Herrero, María de los Ángeles (Scripta, 2023)
This paper is an approach to the research work of religious women with a reputation for sanctity, nuns with a mystical profile, and writers in obedience of the spiritual confessor who are framed within the stream of publications of saints' lives and hagiographic repertoires, of great apogee in the Early modern age. Teresa de San Bruno (1655-1722) abbess, monastery founder and biographer by obedience becomes an example of a religious who participated in the enterprise of the writings under the mandate of the confessor, but as an observer of Gertrudis María de la Santísima Trinidad (1660-1736).